PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKn DENGAN METODE BERMAIN PERAN KELAS IV SEKOLAH DASAR - Fitriati, Fitriati; reinita, reinita; lubis, mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
ABSTRACT The purpose of this study is to increase student learning outcomes in Civics Learning with Class IV Elementary Role Playing Methods. This type of research is Classroom Action Research. The research subjects were 26 people. The results of the observation of RPP cycle I increased in cycle II with an average value of 87% good qualification. The aspect of teacher observation in cycle I increased in cycle II with an average score of 86% good qualification. Means, the Learning Model of Role Playing Methods can improve the learning process of fourth grade elementaryschool. . Kata Kunci : Hasil Belajar PKn: Metode Bermain Peran